Do misery and happiness both love company? The emotional consequences of listening to experiences shared by others. - Samantha Warchol (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
Sharing personal experiences and events is an important component of developing personal relationships and connecting with others. Two adages present contradictory thoughts on how “friends” will respond to personal accomplishments or difficulties. The first claims, “When times get rough, you will find out who your real friends are”; the other claims, “Misery loves company”. This study focuses on how sharing information affects individual mood in order to understand how sharing a personal experience may affect relationships and listeners. Previous research has focused on how the speaker potentially benefits from sharing personal experiences with others. Instead, this study attempts to understand how the listener is affected emotionally by having an event shared with them; do people typically enjoy hearing about others’ happiness or do people relish in the misery of others? The “Personal Experiences Survey” functions as a preliminary measure that asks participants to first act as a “speaker” in sharing their own personal experience and then asks them to be a “listener” and read another individual’s personal experience. Participants’ moods are measured both after acting as the “speaker” and as the “listener” in order to detect overall mood changes. The participants with the greatest increase in positive mood were those who shared their own positive experience and then read a positive experience; participants also preferred listening to events congruent to their present mood. Overall, this study shows that individuals focus on their own experiences, minimizing the experiences of others unless they, as a listener, benefit.